IMPLEMENTASI BLOCKCHAIN DALAM APLIKASI PEMILU - Pratama, Yulfitno Wingga; Kurniadi, Denny (INCARE, International Journal of Educational Resources, 2021)
Elections are a democratic activity in Indonesia which are carried out every five years to elect leaders, but in the process of manual election calculations, the results are leaked and can cause data security problems. Through this research, we can provide solutions by implementing blockchain technology in election applications that will provide security for election results data stored on the blockchain. Blockchain technology is a chain of data blocks that are connected to each other by peer to peer. This application uses the Solidity programming language and uses a local ethereum blockchain database (Ganache). The method used in making this application is the waterfall method with Unified Modeling Language (UML) modeling where the visual modeling method is in object-oriented system design. From the results of testing the blockchain system for this application, it is found that blockchain can help secure election results very securely, where every result data will be stored in every block in a decentralized blockchain network.